Identification of Ferroptosis-Related Genes as Biomarkers for Sarcoma - Guan, Zhiyuan; Liu, Shengfu; Luo, Liying; Wu, Zhong; Lu, Shan; Guan, Zhiqiang; Tao, Kun (Frontiers in Cell and Developmental Biology, 2022)
Sarcoma is characterized by genetic and transcriptional heterogeneity and poor prognosis. Although the genes involved in ferroptosis are still unclear, iron loss is considered to be the core of glioblastoma, tumor progression, and tumor microenvironment. Here, we developed and tested the prognosis of SARC, which is a genetic marker associated with iron residue. Using differential gene expression analysis, one-way Cox analysis, and least-selection absolute regression algorithm (LASSO), select genes related to prognosis combined with cytomegaly and develop risk assessment models. Finally, use immune system infiltration and immune control point analysis to study the characteristics of the tumor microenvironment related to risk assessment. besides, LncRNA-miRNA-mRNA network was contributed in our studies. We determined the prognostic characteristics associated with iron degradation in gene 32 and developed a risk assessment model. ROC analysis showed that the risk assessment model accurately predicted 1, 2, 3, 4, and 5 years of overall survival in the TCGA cohort of SARC patients. Comparative environmental analysis showed that the overall survival rate of the high-risk group was significantly lower than that of the low-risk group (P < 0.0001). TThe nomogram survival prediction model has a strong ability to predict the overall survival of SARC patients. TCGA shell. GSEA analysis showed that inflammation, tumor-related signals and disease processes were enriched in the high-risk group. High risk is related to immune cell infiltration and expression of immune checkpoint. Our prediction model is based on SARC ferritin-related genes, which may support SARC prediction and provide potential attack points.